Association of the human leucocyte antigen region with susceptibility to Parkinson's disease. Issue 8 (12th May 2010) - Saiki, Misuzu; Baker, Amie; Williams-Gray, Caroline H; Foltynie, Thomas; Goodman, Reyna S; Taylor, Craig J; Compston, D Alastair S; Barker, Roger A; Sawcer, Stephen J; Goris, An
Abstract : Objective: The core pathology of Parkinson's disease (PD) is a loss of the dopaminergic neurons in the nigro-striatal pathway, but this is only part of a more widespread pathological process, the nature of which is unknown. Recent data suggest a possible role for inflammation in this disease process. The Human Leucocyte Antigen (HLA) region is one of the most important genetic susceptibility factors in many immune-mediated diseases but has not been extensively investigated in PD. Methods: The authors typed the HLA class II loci HLA-DRB1 and -DQB1 in 528 patients with Parkinson's disease and 3430 controls from the UK. Results: The authors observed an association of HLA-DRB1 with susceptibility to Parkinson's disease. In particular, HLA-DRB1*03 was more common in patients compared with controls. Conclusions: These data suggest a possible role of the HLA region in susceptibility to Parkinson's disease and as such are consistent with other evidence supporting the role of an inflammatory process in the cellular loss in Parkinson's disease, especially of the nigral dopaminergic neurons.